Analysis Speech Function Used in A Movie “Frozen II” - Ni Made Putri Sinta Dewi (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
This paper aimed to identify speech functions used in the Frozen II movie.The data was taken from the dialogues in the Frozen II movie. The data was collected by identifying, note taking, classifying and counting the percentage of speech function in this movie. The data shows that this movie used expressive function 47%, directive function 31%, and referential function 22%. The expressive function is usually used to express the character’s feelings or ideas, the directive function used to get the other character to do something and referential function used to get or give information. The researcher hopes that this paper will help the next researcher of speech function to develop their research.